2020
DOI: 10.1007/s10980-020-01141-2
|View full text |Cite
|
Sign up to set email alerts
|

Grassland-to-crop conversion in agricultural landscapes has lasting impact on the trait diversity of bees

Abstract: Context Global pollinator decline has motivated much research to understand the underlying mechanisms. Among the multiple pressures threatening pollinators, habitat loss has been suggested as a key-contributing factor. While habitat destruction is often associated with immediate negative impacts, pollinators can also exhibit delayed responses over time. Objectives We used a trait-based approach to investigate how past and current land use at b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 62 publications
1
9
0
Order By: Relevance
“…In our study, we measured continuous morphological traits on our sampled individuals. We found that carabid species, traits in arable field communities differentiate along three main dimensions of functional specialization, similar as previously shown for other taxa (Le Provost, Badenhausser, Le Bagousse-Pinguet, et al, 2020).…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…In our study, we measured continuous morphological traits on our sampled individuals. We found that carabid species, traits in arable field communities differentiate along three main dimensions of functional specialization, similar as previously shown for other taxa (Le Provost, Badenhausser, Le Bagousse-Pinguet, et al, 2020).…”
Section: Discussionsupporting
confidence: 88%
“…Dispersal-related traits might be filtered by landscape spatiotemporal structure. It has been previously shown that long-term land-use change to more intensive agricultural landscapes has impoverished the functional diversity of mobility traits in carabid assemblages (Le Provost, Badenhausser, Le Bagousse-Pinguet, et al, 2020), and selected species with higher dispersal abilities and tolerance against agricultural disturbances (Turin & Den Boer, 1988). Secondly, in some species, macropterous individuals do not necessarily possess functioning flight muscles and are therefore incapable of flight (Desender & Turin, 1989; Nelemans, 1987), at least at certain periods of their life cycle (Van Huizen, 1977).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations